Determinants Of Culinary Enterprise Prosperity And Its Contribution To Regional Incomein The City Of Samarinda - Dwi Haryanti; Jiuhardi Jiuhardi; Juliansyah Roy (Pusat Riset dan Inovasi Nasional, 2023)
The Aim Of This Research Is To Determine The Contribution Of Culinary Business Actors To Regional Income And Influencing Factors In The City Of Samarinda. This Research Uses A Quantitative Analysis Approach That Adopts Partial Least Square (PLS). PLS Is A Powerful Analysis Method Because It Is Not Based On Many Assumptions. Based On The Findings, It Shows That Social Capital Is The Variable That Has The Greatest Influence, Both Directly On Business Performance And The Welfare Of MSME Actors. This Can Be Proven By The Largest Estimated Coefficient. For This Reason, Social Capital Is The Most Important Factor To Pay Attention To In Improving The Welfare Of Culinary Business Actors In Samarinda. The Emergence Of A Sense Of Solidarity That Small Businesses Are A Form Of Small Economic Activity That Is Able To Survive Amidst The Difficulties Of The Indonesian Economy Indicates The Role Of Social Capital In The Community's Economy. It Is Called Social Capital, Because Starting Small And Micro Business Activities Usually Starts With Information From Relatives, Friends, Neighbors Or Family Who Have Tried Before. They Help Each Other With Capital, Supply Of Raw Materials, Housing And Information, Such As Business Location Information, Capital Loans.